2019
DOI: 10.1021/acs.chemmater.9b01508
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Single-Crystalline Lead Sulfide Nanoframes and Nanorings

Abstract: We present a colloidal synthesis strategy to obtain single-crystalline PbS nanorings. By controlling the ripening process in the presence of halide ions, a transformation of initial PbS nanosheets to frame-like structures and finally to nanorings was achieved. We found that the competing ligands oleic acid, oleate and halide ions play an important role in the formation of these nanostructures. Therefore, we propose a formation mechanism based on a thermally induced ripening of crystal facets dependent on the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…We remark here that these shapes all belong to the genus = 0 class. Reports in the literature on the synthesis of colloidal quantum rings, i.e., with a genus of 1 topology, recently emerged. …”
Section: Introductionmentioning
confidence: 99%
“…We remark here that these shapes all belong to the genus = 0 class. Reports in the literature on the synthesis of colloidal quantum rings, i.e., with a genus of 1 topology, recently emerged. …”
Section: Introductionmentioning
confidence: 99%
“…As known, halide ions released from halide alkanes are the actually functioning ligands instead of the original halide alkanes themselves in IV-VIA group semiconductors. [27] By means of the specific binding preference on crystal surfaces, or the complexation with metal atoms, or the etching process, halide ions have been proven as good optional ligands for obtaining 2D nanostructures in solution. [22,24,28] Further, we found that for the NS formation, halide ions can be introduced from salts such as LiCl or LiBr dissolved in dimethylformamide (DMF) and added to the reaction flask.…”
Section: Resultsmentioning
confidence: 99%
“…Note, the occurrence of the etching on SnTe is assumed to be mainly due to the change of the chemical environment when the tin chloride/bromide is used. [27] The salt addition into the reaction can affect the polarity of the solvent. Further, it also alters the capping conditions of the organic ligand layers on the crystal surface, which triggers the etching process when the ligand layer conditions change, followed by a change of the solubility of SnTe.…”
Section: Resultsmentioning
confidence: 99%
“…Elemental analysis was performed via energy-dispersive X-ray (EDX). Lead sulfide nanoframes can be synthesized by the one-pot synthesis method [52]. Lead acetate trihydrate, oleic acid, and diphenyl ether were all mixed in a round-bottomed flask and degassed at 7 • C for 2 h. During heating at 22 • C (lithium chloride dimethylformamide), LiCl-DMF solution was added.…”
Section: One-pot Synthesismentioning
confidence: 99%